Inaccuracy of Diction in Arrangements by Class VII Students of Daar El Arqam Mauk Islamic Middle School - Ahmad Hidayatullah; Nini Ibrahim; Fauzi Rahman; Ahmad Muzaki (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Diction is the most important aspect in determining sentence clarity. Through diction, a person can develop ideas in his descriptive essay. Therefore, the purpose of this study was to examine the inaccuracy of diction in students' descriptive essays, and to describe the results of the research as learning materials. This research method is a qualitative description method. This research was conducted by analyzing students' descriptive essays based on the inaccuracy of diction in the sentences used. The results of this study indicate that there are students' inaccuracies in using diction, namely 53 inaccuracy of diction based on lexical meaning, 34 grammatical meanings, 12 use of synonyms, and 4 uses of denotation and connotation. The conclusion in this study is that the students' ability to use diction has not been properly used in the descriptions they made.Keywords: Inaccuracy, Diction, Arrangements